A New Design Of Navigation Light Using Wave Energy. (November 2020) - Li, Yuze
Abstract: Numerous floating beacon lights are distributed along the coast and inland waterways. Beacon light is a kind of traffic light that is installed on some beacon to provide safety for ships traveling at night. Beacon lights mostly use batteries as power sources, and some use wind and mechanical energy to convert into electrical energy. Large lighthouses mostly use diesel engines. As a renewable and clean energy, wave energy provides a new solution to the continuous power supply needs of floating beacon lights. We have designed a new beacon light device using wave energy. The device uses low-frequency irregular wave energy to convert to high-frequency stable mechanical vibration required for power generation, and then uses piezoelectric power generation technology to convert mechanical energy into electrical energy and store it to power the floating navigation light.